2022
DOI: 10.1101/2022.11.09.515507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune Response following FLASH and Conventional Radiation in Diffuse Midline Glioma (DMG)

Abstract: Purpose Diffuse Intrinsic Pontine Glioma is a fatal tumor traditionally treated with radiotherapy (RT) and previously characterized as having a non-inflammatory tumor immune microenvironment (TIME). FLASH is a novel RT technique using an ultra-fast dose-rate which is associated with decreased toxicity, effective tumor control and potential immune-sparing properties. However, the effect of FLASH on the DIPG tumor immune microenvironment (TIME) has not yet been explored. Methods Here, we perform single-cell RNA … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…This approach has garnered significant recent attention due to its normal tissue sparing effects and represents a possible avenue for RT dose-escalation or dose-painting that merits further investigation [ 64 ]. Moreover, recent work has suggested that FLASH RT may also have immunologic implications, with two recent reports suggesting that FLASH RT can upregulate T-cell activating and trafficking markers in both glioblastoma and diffuse pontine glioma models [ 65 , 66 ].…”
Section: Roadmap To Clinical Translationmentioning
confidence: 99%
“…This approach has garnered significant recent attention due to its normal tissue sparing effects and represents a possible avenue for RT dose-escalation or dose-painting that merits further investigation [ 64 ]. Moreover, recent work has suggested that FLASH RT may also have immunologic implications, with two recent reports suggesting that FLASH RT can upregulate T-cell activating and trafficking markers in both glioblastoma and diffuse pontine glioma models [ 65 , 66 ].…”
Section: Roadmap To Clinical Translationmentioning
confidence: 99%